Influência da orientação de prototipagem no comportamento mecânico da liga Ti-6Al-4V produzida por sinterização direta de metal por laser (DMLS) - Britto, Carlos Eduardo Silva [UNESP] (2015)
This work has as objective to realize analysis of the mechanical and microstructural properties of Ti-6Al-4V alloy components produced by the Direct Metal Laser Sintering (DMLS) process that is based on the deposition of a metal powder layers and posteriorly fused by a high power laser beam. Therefore, components were produced in three different orientations (A, B and C) in order to verify the influence of the layers deposition on the mechanical properties and fracture micromechanisms, through the tensile tests, fatigue and tenacity of fracture and scanning electron microscopy (SEM). The samples were also subjected to a heat treatment to relieve residual stresses resulting from the manufacturing process and after analyzed through a optical microscopy and X-ray diffraction, to ascertain if there were changes in the microstructure or phase decomposition in relation to a sample without a heat treatment and at as manufactured condition. The construction orientation B and C have had better values in all mechanical tests when compared to the orientation A, revealing that had a loss of mechanical strength, except in the microhardness test, where the average values did not have large variations in the orientation of manufacturing. The sample as manufactured presented higher hardness values when compared to samples with treatment to relieve the residual stress, and this fact occurred due the precipitation of the B phase and the growth of the a phase in the material, which initially had a structure consisting of martensite hexagonal (a')